Tingkat Kepuasan Mahasiswa Dalam Menggunakan Sistem Informasi Akademik Universitas Negeri Gorontalo Menggunakan PSSUQ - Auliyani, Andi Sitti Dwi; Sakti, Angga Yuda; Susiati, Devi; Mohamad, Silvana (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to measure the level of user satisfaction, specifically among Industrial Engineering students, with the Academic Information System of Universitas Negeri Gorontalo (SIAKAD UNG) using the Post Study System Usability Questionnaire (PSSUQ) method. Data were collected by distributing an online questionnaire to 63 student respondents. The results show an overall average score (Overall) of 3.88 (on a 1-5 scale), indicating a positive level of user satisfaction. Information Quality (InfoQual) achieved the highest score (3.89), followed by System Usefulness (SysUse) at 3.85, and Interface Quality (IntQual) at 3.78. The key finding reveals that the system's strength lies in its information quality, while the user interface is the aspect most in need of improvement to enhance the overall user experience. The results of this study are expected to serve as an empirical reference for the development and quality improvement of SIAKAD UNG services.